Developing the strategic collaboration model in basic education - Mashuri H. Tahili; Ismail Tolla; Muhammad Arifin Ahmad; Sulaiman Samad; Abdul Saman; Pattaufi Pattaufi (Institute of Advanced Engineering and Science, 2022)
The strategic collaboration approach has recognized widely can overcome the complexities and challenges of teaching and learning programs and achieve sustainable education quality improvement. This study analyzed the development of a strategic collaboration approach in education at local government in Indonesia. The mixed-method analyzed the correlation of the strategic collaboration approach in education. Data gained through the questionnaire for quantitative data and in-depth interview with the key informants for qualitative data. The school collaboration networks, school strategic leadership, teacher strategic alliances capacity, school culture innovation, and school committee collaboration. Besides, the education service innovation as the core objective of the element education strategic collaboration has determined by two factors consist of school collaborative strategic planning and strategic collaboration development in education. Research samples were teachers, school leaders, and school supervisors and also the personnel of the education agency of Banggai Regency, Central Sulawesi, Indonesia. The research samples selected by using a stratified random sampling technique. There were 521 selected respondents and 15 key informants. The questionnaires for quantitative model are scaled on a 6 point-Likert scale ranged from strongly agree to strongly disagree. The strategic collaboration development model viewed as a better approach to achieve education quality improvement, creating a service innovation, and quality control in education.